Gay, Inc. : the nonprofitization of queer politics - Beam, Myrl (Univiversity of Minnesota Press, 2018)
"Gay, Inc. investigates the massive expansion of the non-profit system since the mid-1960s, and the impact this expansion has had on queer social movements. Based on ethnography and oral histories as well as archival research, it looks at how people at four LGBT non-profits in the Midwest grapple with the contradictions between the radical imaginary of queer social movements and their institutionalized iterations. Beam argues that the institutional form of queer social movements informs and structures the politics that can be articulated from within them, and that the shift in focus towards marriage and formal legal equality is due, in large part, to the LGBT movement's embrace of the non-profit structure"--